Socio-emotional Competence and Adjustment of Students in COVID-19 Rethinking School-based Learning - Rajagopalan, Jaya (JOURNAL OF INDIAN EDUCATION, 2022)
The COVID-19 pandemic has created an unprecedented mental health crisis, posing a unique challenge to global psychological resilience. In this context, this study focused on understanding the significance of socio-emotional competencies on students’ mental health and wellness during COVID-19. Validated instruments measuring emotional competence, social competence, life satisfaction and adjustment were used to collect data from 210 adolescents (13–14 years). Results showed that during the pandemic, nearly one-third of the students reported inadequate social, emotional and educational adjustment. The ability to manage difficult emotions, which is critical for work and life success, had the lowest score on the emotional competence dimension. Regression analysis showed the significant role of social and emotional competencies in explaining the variance in adjustment. This study strengthens and outlines the need to include socio-emotional learning interventions into educational programmes at school, especially in the context of COVID-19 pandemic.